The relationship between childhood psychological abuse and cyberbullying behavior among graduate students: the mediating role of negative coping style and trait anxiety - Shen, Yi (Frontiers in Psychiatry, 2024)
BackgroundAs a major public health problem, cyberbullying has been received widespread attention in recent years. However, most researches on cyberbullying are mainly focused on adolescents and college students, the underlying mechanisms of cyberbullying among graduate students have been relatively less investigated. From the perspectives of the general aggression model and attachment theory, this study aims to explore the relationship between childhood psychological abuse and cyberbullying behavior among graduate students, as well as the mediating roles of negative coping style and trait anxiety.Materials and methodsA total of 482 graduate students were surveyed using measures including the Childhood Psychological Abuse Scale, Simplified Coping Style Questionnaire, Self-Rating Anxiety Scale, and Cyberbullying Behavior Scale.Results(1) There were significant positive correlations between childhood psychological abuse, negative coping style, trait anxiety, and graduate students’ cyberbullying behavior; (2) Childhood psychological abuse could forecast graduate students’ cyberbullying behavior through the mediating effects of negative coping style and trait anxiety. This mediation process includes two pathways: the independent mediating effect of negative coping style and the chained mediating effect of negative coping style and trait anxiety.ConclusionNegative coping style and trait anxiety play mediating roles in the relationship between childhood psychological abuse and cyberbullying behavior among graduate students.